The public perception and adaptability of laws and regulations of autonomous driving vehicles - Yichuan Yang; Zongyu Song (Humanities & Social Sciences Communications)
Abstract This study aims to explore the public’s attitude towards the development of autonomous vehicles and their perception of the adaptability of existing laws and regulations, and to analyze the interactive relationship between social acceptance and policy making. The study conducts questionnaire surveys to collect opinions from the public in specific regions, and combines legal text analysis to evaluate the responsiveness and flexibility of existing laws and regulations to autonomous driving technology. The study found that the public is cautiously optimistic about autonomous vehicles, but has obvious concerns about issues such as the definition of their legal responsibilities, safety assurance mechanisms, and privacy protection. At the same time, the current laws and regulations have obvious lags in technical standards, test access, and responsibility division, and it is difficult to fully meet the needs of the rapid development of autonomous driving technology. The important contribution of this study is that it systematically combines public opinions with legal adaptability assessments for the first time, providing empirical evidence for policymakers, emphasizing that while promoting technological development, the dynamic adjustment of laws and regulations and the establishment of public communication mechanisms should be promoted simultaneously, so as to build a social and institutional environment conducive to the healthy development of autonomous driving technology.